In memoriam: Maurizio Tosi, 1944–2017 - Frenez, Dennys; Cattani, Maurizio (Proceedings of the Seminar for Arabian Studies, 2017)
Maurizio Tosi, a giant of archaeology, died in Ravenna on 24 February 2017 as a result of heart failure. His contribution to archaeology as a science and to the development of archaeological activities at the Sultanate of Oman was immense. From the mid-1970s, he carried out numerous seminal projects in Iran, Oman, Yemen, Pakistan, India, Uzbekistan, Turkmenistan, Tajikistan, Mongolia, Egypt, Tunisia, Italy, and the United States. Moreover, thanks to his immense knowledge of culture and a constant desire to learn, he was a pioneer of multi-disciplinary archaeology, using bio-archaeology and geo-archaeology from the early stages of his career and introducing Geographic Information Systems (GIS) and remote-sensing applications before most of his colleagues. His work on the interactions between humans and environment contributed greatly to the theoretical foundation of archaeology and to the development of ‘New Archaeology’ paradigms.